The Influence of School Religious Cultural Habituation on Students' Religious Knowledge - Dina Amalia; Ade Ismatullah; Teguh Hariyanto (Interpersonal: Jurnal Bimbingan Konseling Islam, 2025)
This study is motivated by the decline in religious understanding among adolescents, even though they attend Islamic-based schools. Data from 2025 indicate several obstacles: 33.87% of students are unable to distinguish between pillars, sunnah, and conditions of worship; 53.23% make mistakes in tajwid and fail to comprehend the meaning of verses; 64.52% focus only on memorizing hadith without understanding their substance; and 24.19% have not mastered the sequence of worship. Furthermore, 83.87% are passive in religious activities, and 64.52% score below the Minimum Mastery Criteria (KKM). This raises the question of how far the habituation of religious culture in schools influences students’ religious knowledge. The objectives of this study are to identify the implementation of religious culture in schools, to measure the level of students’ religious knowledge, and to analyze the influence between the two. The research employed a quantitative approach with a descriptive method and correlational design using simple linear regression analysis. The study population consisted of 163 students, with a sample of 62 students determined through the Slovin formula. Data were collected through questionnaires, observation, interviews, and documentation, and analyzed using validity, reliability, normality, linearity tests, and regression with SPSS. The results show that religious culture in schools has been well implemented, students’ religious knowledge is categorized as good, and there is a positive and significant influence between the two. Thus, religious culture proves to be an important factor in enhancing students’ religious understanding both theoretically and practically.